Assessing the influence of the color of the plate on the perception of a complex food in a restaurant setting - Piqueras-Fiszman, B; Giboreau, A; Spence, C (BioMed Central, 2013)
Background Nowadays, more and more importance is given to how restaurant dishes are visually presented. With regard to the color of the plate, several recent studies have demonstrated that identical foods served on plates (or in containers) of different colors are often perceived differently at both the sensorial and hedonic levels. However, to date, these effects have not been tested in an ecologically valid setting with a range of more complex foods in order to assess the generalizability of the findings. The aims of the present study were to test the extent to which the color of the plate may influence the gustatory and hedonic experiences of a complex food. Specifically, we investigated diners’ perception of three desserts served on a white or black plate in a between-participants experimental design in a real restaurant setting. Results The results demonstrated that the color of the plate exerted a significant influence on people’s perception of the food, but that this effect varied as a function of the type of dessert served. The effects cannot be explained only in terms of color contrast. Color-flavor associations, for example, black with intense chocolate flavor, or even sophisticated chocolate, could have an impact too. Interestingly, the perceptual pattern for each dessert was constant for each plate used; that is, for all of the attributes rated, the higher scores were obtained with the same plate, for all of the desserts. Conclusions These results confirm the importance of the color of the plate (or background color) on people’s expectation and perception of food, even in realistic and less controlled conditions, such as that of a restaurant.